Modeling shock waves in orthotropic elastic materials - Vignjevic, Rade; Campbell, James C.; Bourne, Neil K.; Djordjevic, Nenad (American Institute of Physics (AIP), 2008)
A constitutive relationship for modeling of shock wave propagation in orthotropic materials is proposed for nonlinear explicit transient large deformation computer codes (hydrocodes). A procedure for separation of material volumetric compression (compressibility effects equation of state) from deviatoric strain effects is formulated, which allows for the consistent calculation of stresses in the elastic regime as well as in the presence of shock waves. According to this procedure the pressure is defined as the state of stress that results in only volumetric deformation, and consequently is a diagonal second order tensor. As reported by Anderson et al. [Comput. Mech.15, 201 (1994)], the shock response of an orthotropic material cannot be accurately predicted using the conventional decomposition of the stress tensor into isotropic and deviatoric parts. This paper presents two different stress decompositions based on the assumption that the stress tensor is split into two components: one component is due to volumetric strain and the other is due to deviatoric strain. Both decompositions are rigorously derived. In order to test their ability to describe shock propagation in orthotropic materials, both algorithms were implemented in a hydrocode and their predictions were compared to experimental plate impact data. The material considered was a carbon fiber reinforced epoxy material, which was tested in both the through-thickness and longitudinal directions. The psi decomposition showed good agreement with the physical behavior of the considered material, while the zdeta decomposition significantly overestimated the longitudinal stresses.